Justice 2.0: Street harassment victims’ use of social media and online activism as sites of informal justice - Fileborn, Bianca (The British Journal of Criminology, 2017)
Emerging scholarship has considered the potential for online spaces to function as sites of informal justice. To date, there has been little consideration of the experiences of individuals who seek justice online, and the extent to which victims’ justice needs can be met online. Drawing on the findings of a mixed-methods research project with street harassment victims in Melbourne, Australia, I consider participants’ reasons for, and experiences of, disclosing their encounters of street harassment online. I examine the extent to which these ‘map on to’ a selection of victim’s justice needs. While it is evident that online spaces can function as sites of justice, it is vital to ask for whom and in which contexts justice can be achieved online.

‘Staff can't be the ones that play judge and jury’: Young adults’ suggestions for preventing unwanted sexual attention in pubs and clubs - Fileborn, Bianca (Australian & New Zealand Journal of Criminology, 2017)
This paper explores young adults' suggestions for preventing unwanted sexual attention in licensed venues. Despite emerging evidence that unwanted sexual attention and sexual violence are significant issues faced by young adults in the night-time economy, there has been little introduced in the way of preventative strategies or campaigns. Drawing on a mixed-methods research project undertaken in Melbourne, Australia, I contend that exploring young adults' suggestions for prevention is instructive in a number of ways. Young adults are the primary users of licensed venues and thus may provide insight into potential strategies for prevention. It can also illuminate the discursive positions that young adults draw on in talking about prevention and their understandings of unwanted sexual attention.
Keywords: Camille